Genetic characterization of popcorn hybrids based on SNP genotyping and development of rapid ARMS based primers - Choi, Jae-Keun; Park, Jong-Yeol; Ryu, Si-Hwan; Namgung, Min; Kim, Moon-Jong; Han, Jeong-Heon; Sharma, M. M. M.; Choi, Seon-Kang; Choi, Ik-Young; Ramekar, Rahul Vasudeo; Park, Kyong-Cheul (Journal of Crop Science and Biotechnology, 2021)
In South Korea, popcorn consumption may have boomed in recent years but little has changed little for farmers or breeders. The majority of popcorn sold in the domestic market is derived from imported hybrids. The efforts are needed to identify parental lines and develop hybrids suitable for domestic conditions. However, the major constraint remains a narrow germplasm pool. Thus, knowledge of genetic variability among germplasm as well as among commercial hybrids is important to avoid genetic uniformity, thereby reducing the risk of vulnerability to stress and yield loss. Recently, the Maize Research Institute in Hongcheon developed valuable breeding material: ‘G-popcorn’, a new hybrid, together with ‘Oryun popcorn’, ‘Oryun popcorn2′, and ‘Gichan popcorn’. In this study, we assessed the genetic relationships among domestic and imported hybrids using 55 k single-nucleotide polymorphism (SNP) markers. Approximately 80% of the SNP markers were highly informative for future routine and low-cost genotyping. Considerable polymorphism among the SNP markers was observed with regard to reproducibility, ease of scoring, and minor allele frequency. Broad genetic diversity was detected among the germplasm analyzed; cluster analysis revealed the presence of two distinct groups of hybrids and generally agreed with pedigree information. In addition, we demonstrated the conversion of bead-chip SNP alleles into species-specific primers and used the ARMS-PCR technique to differentiate imported and domestic popcorn hybrids. The developed method will be useful for rapid and cost-effective identification of genetic purity among popcorn hybrids.